2017
DOI: 10.1371/journal.pntd.0005522
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and enumerating soil-transmitted helminth eggs in soil: New method development and results from field testing in Kenya and Bangladesh

Abstract: Globally, about 1.5 billion people are infected with at least one species of soil-transmitted helminth (STH). Soil is a critical environmental reservoir of STH, yet there is no standard method for detecting STH eggs in soil. We developed a field method for enumerating STH eggs in soil and tested the method in Bangladesh and Kenya. The US Environmental Protection Agency (EPA) method for enumerating Ascaris eggs in biosolids was modified through a series of recovery efficiency experiments; we seeded soil samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 38 publications
(48 reference statements)
4
81
0
3
Order By: Relevance
“…Therefore, the distribution of eggs in the soil (Ascaris, Trichuris) in Bangladesh was 78%, and 37% in Kenya, with the average egg concen-tration in soil 0.59 and 0.15 eggs/g, respectively. The distribution of eggs of helminths in the soil was significantly higher in Bangladesh than in Kenya (Steinbaum et al, 2017). Other studies have shown that of 1,480 soil samples, 460 (31%) were positive for the presence of eggs of helminths.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, the distribution of eggs in the soil (Ascaris, Trichuris) in Bangladesh was 78%, and 37% in Kenya, with the average egg concen-tration in soil 0.59 and 0.15 eggs/g, respectively. The distribution of eggs of helminths in the soil was significantly higher in Bangladesh than in Kenya (Steinbaum et al, 2017). Other studies have shown that of 1,480 soil samples, 460 (31%) were positive for the presence of eggs of helminths.…”
Section: Discussionmentioning
confidence: 75%
“…The invasion of parasites, when discharged with feces into the environment, pollutes the soil, water, vegetation and can persist for a long time (Paller & de Chavez, 2014;Tun et al, 2015;Dolbin & Khayrullin, 2017). Exogenous forms of helminths in the environment are represented by eggs and free-living invasive larvae (Blaszkowska et al, 2011;Mohd Zain et al, 2013;Steinbaum et al, 2017), posing a serious hygiene problem (Amadi & Uttah, 2010;Shalaby et al, 2010;Ngui et al, 2012). The main goal of veterinary sanitation is prevention of infectious and parasitic diseases of humans and animals, reduction of ecological pollution of the environment, including water, soils, feed and livestock products, elimination of epizootic outbreaks by means of disinfection, disinfestation, disinsection and deratization (Backhans & Fellström, 2012;Paliy et al, 2016;Spanu et al, 2016;Paliy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Enteric parasites are transmitted through ingestion or skin contact with infectious stages in soil, water and food, in a fecally-contaminated environment. Most transmission is considered to occur around or within households [9,10]. Here, using a sensitive and specific molecular method to detect a range of intestinal parasites, we show for the first time, a potential new source of transmission of these parasites from within the household, especially in bed dust.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have sampled for presence of infectious parasite stages as sources of transmission around households including latrines [6,7] and within houses [8][9][10] but none to our knowledge have used sensitive molecular methods to detect specific parasite DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic tests with greater specificity and sensitivity are crucial to successfully detect the presence of Ascaris ova in recycled water prior to release for public use [53]. Such a test will also help to monitor the transmission of ascariasis in endemic and low resource setting areas.…”
Section: Discussionmentioning
confidence: 99%